Experimental study of performance and prototype of elliptical altitude detection based on global navigation satellite system - Zulfikar, Dwi Aji; Nurkarya, Yoyok; Setiyadi, Johar; Kurniawan, Endro Sigit; Carudin, Carudin; Suhadi, Suhadi (Institute of Advanced Engineering and Science, 2025)
Global navigation satellite system (GNSS) is a multi-satellite-based navigation system, in the GNSS positioning process involves several navigation satellites such as global positioning system (GPS) which is a navigation system to bring up more observation data so that it is very useful when determining the desired parameters in a real-time data processing. In the research, an experimental study is used to determine land subsidence which is one of the vertical deformations of the earth's crust as a consequence of crustal dynamics. The result of the analysis is raw position data with the average method of detecting the height of the ellipsoid in the XYZ location area. Data collection is done by observation using the absolute method for one hour for position and fifteen days of observation for height. While the equipment used is u-blox Neo-7M, MCU TTL RS-485 module, ESP32-S Dev Kit V1 module, memory card module and real time clock (RTC). The results of the observation validation analysis are i) GPS-1 Easting 1.09 m and Northing 1.08 m, GPS-2 Easting 1.19 m and Northing 1.32 m, GPS-3 Easting 0.54 m and Northing 0.64 m while GPS-AVG GPS Easting 0.56 m and Northing of 0.64 m, ii) The results of the GPS-1 ellipsoid height analysis are 3.76 m, GPS-2 4.28 m, GPS-3 of 3.69 m, and iii) GPS AVG of 3.01 m.